Potential of constructed wetlands for removal of antibiotics from saline aquaculture effluents - Bôto M. (2016)
This work aimed to evaluate the potential of constructed wetlands (CWs) for removal of antibiotics (enrofloxacin and oxytetracycline) and antibiotic resistant bacteria from saline aquaculture wastewaters. Removal of other contaminants (nutrients, organic matter and metals) and toxicity reduction and the influence of antibiotics with these processes were evaluated. Thus, nine CWs microcosms, divided into three treatments, were assembled and used to treat wastewater (doped or not with the selected antibiotics) between October and December of 2015. Each week treated wastewater was removed and new wastewater (doped or not) was introduced in CWs. Results showed > 99% of each antibiotic was removed in CWs. After three weeks of adaptation, removal percentages > 95% were also obtained for total bacteria and for antibiotic resistant bacteria. Nutrients, organic matter and metal removal percentages in CWs treated wastewater were identical in the absence and in the presence of each antibiotic. Toxicity in treated wastewaters was significantly lower than in initial wastewaters, independently of antibiotics presence. Results showed CWs have a high efficiency for removing enrofloxacin or oxytetracycline as well as antibiotic resistant bacteria from saline aquaculture wastewaters. CWs can also remove other contaminants independently of drug presence, making the aquaculture wastewater possible to be reutilized and/or recirculated. © 2016 by the authors.